2021
DOI: 10.1111/jep.13570
|View full text |Cite
|
Sign up to set email alerts
|

Are patients really getting what they want? The routine implementation of decision aids for patients with hip or knee osteoarthritis in the high value healthcare collaborative and alignment between patient treatment choice and receipt

Abstract: Rationale, Aims and Objectives Alignment between patients' treatment choices and treatments received is acknowledged as an important outcome of shared decision‐making (SDM), yet recent research suggests that patients' choices do not always align with their actual treatment trajectories. This paper explores the alignment of patient‐expressed treatment choices (for surgery or medical management) after exposure to decision aids and treatments received among patients with hip or knee osteoarthritis within High Val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Although the overall report content was satisfactory for most participants, individuals attributed differential value to data elements and their presentation, which was often associated with stage of disease or decision regarding surgery. Similarly, varying benefits across the decision‐making continuum have been reported for non‐personalized hip/knee OA decision reports 31 . Additionally, trial surgeons in our study also reported differential use and value of different report sections 32 .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Although the overall report content was satisfactory for most participants, individuals attributed differential value to data elements and their presentation, which was often associated with stage of disease or decision regarding surgery. Similarly, varying benefits across the decision‐making continuum have been reported for non‐personalized hip/knee OA decision reports 31 . Additionally, trial surgeons in our study also reported differential use and value of different report sections 32 .…”
Section: Discussionsupporting
confidence: 73%
“…Similarly, varying benefits across the decision-making continuum have been reported for nonpersonalized hip/knee OA decision reports. 31 Additionally, trial surgeons in our study also reported differential use and value of different report sections. 32 Our combined findings across patients and surgeons suggest that further tailoring could maximize broader report acceptability and perceived relevance.…”
Section: Discussionmentioning
confidence: 62%
“…This calculation is valid only for large populations and is intended to promote discussion with the patient about comparative lost productivity, with the most important point being that productivity loss is highest when the patient “does nothing.” The SDM tool relies on multiple data sources, including the Hospital Cost and Utilization Project, the Behavioral Risk Factor Surveillance System, Truven Health MarketScan Research Databases, the Medicare Expenditure Panel Survey, the National Vital Statistics Report, treatment guidelines from the American Academy of Orthopaedic Surgeons, and treatment effects extracted from systematic literature reviews, meta-analyses of randomized, controlled trials, and published randomized controlled trials,[ 19 ] as well as patient and health care provider focus groups. [ 20 ]…”
Section: Methodsmentioning
confidence: 99%
“…Recognizing the urgent need to address musculoskeletal health disparities, Movement is Life, a multidisciplinary consortium comprising racially and ethnically diverse individuals,[ 16 17 ] created an innovative SDM tool to facilitate discussions between clinicians and patients regarding treatment options for chronic knee pain. As disparities in the treatment of osteoarthritis in diverse populations have been reported,[ 19 ] and these patients may have lower odds of receiving treatment aligned with their choices,[ 20 ] the user-testing specifically recruited African American and Latina women. Primary care providers and family physicians are often the first healthcare providers to become aware of a patient’s symptoms associated with early stage osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation